1993
DOI: 10.1172/jci116468
|View full text |Cite
|
Sign up to set email alerts
|

A fetally expressed immunoglobulin VH1 gene belongs to a complex set of alleles.

Abstract: The immunoglobulin V H gene 51p1, a member of the large V H1 gene family, is preferentially expressed by B cells in the fetus and in chronic lymphocytic leukemia (CLL) and appears to be the source for many cryoglobulin rheumatoid factors. Polymorphism of Sipi may therefore be functionally important. We have studied the germline representation of 51pl and closely related V H elements to establish their prevalence and allelic relationship. A panel of oligonucleotide probes directed to the complementarity determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 47 publications
6
85
0
Order By: Relevance
“…Recently it has been shown that this V H gene, which corresponds to the rearranged 51p1 sequence of the fetal repertoire (20), is present in the genome at varying numbers of copies (44). Using an anti-Id antibody, G6, which reacts with V regions encoded by 51p1 (43), the frequency of G6 ϩ IgD ϩ tonsillar B cells ranged from zero to 11.4% and correlated with the copy number of 51p1-related genes in different donors (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that this V H gene, which corresponds to the rearranged 51p1 sequence of the fetal repertoire (20), is present in the genome at varying numbers of copies (44). Using an anti-Id antibody, G6, which reacts with V regions encoded by 51p1 (43), the frequency of G6 ϩ IgD ϩ tonsillar B cells ranged from zero to 11.4% and correlated with the copy number of 51p1-related genes in different donors (45).…”
Section: Discussionmentioning
confidence: 99%
“…The VH1-69 immunoglobulin segment is expressed in the restricted repertoire of fetal liver B lymphocytes and is thought to be involved in natural immunity. 40,41 A productive VH1-69 rearrangement is present in ϳ1.6% of normal B lymphocytes in adults. 42 VH1-69 is rearranged in ϳ10 to 20% of B-cell chronic lymphocytic leukemia 30,43 and a VH1-69 monoclonal rearrangement is present in the majority of patients with type II mixed cryoglobulinemia, a typical HCV-related disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming an equal expression frequency, the 1263-like alleles would be expected to be present in ϳ30% of V H 1-69-encoded rearrangements. The 1263-like variants primarily differ from 51p1 by only three amino acid substitutions in CDR2 (10). These changes are enough to eliminate binding of the G6 mAb used to define the G6 Id.…”
Section: Discussionmentioning
confidence: 99%
“…51p1 is an Ig V H 1 gene and is one of several alleles that belong to the V H 1-69 H chain locus. Restriction fragment length polymorphism analysis using oligonucleotide probes identified at least 13 distinct variants (10). These variants represent nine related sequences that can be divided into two groups based on several single-base differences in the second complementaritydetermining region (CDR2).…”
Section: B Cell Chronic Lymphocytic Leukemia (Cll) 3 Is Character-mentioning
confidence: 99%